The value of bad ratings: An experiment on the impact of distortions in reputation systems - Claudia Keser; Maximilian Späth (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We study the robustness of reputation management systems against distortions in rating behavior. In a laboratory trust experiment with reputation management, we mimic a positive bias by exclusively offering the option to rate positively or to give no rating. As predicted by theoretical considerations, this bias leads to significantly less trust than a system that additionally offers a negative rating option. A system relying solely on negative ratings does not have such an adverse effect. This highlights the importance of negative ratings for the effectiveness of reputation systems.
Keywords: C91; L14; C73; 330; Trust; Trustworthiness; Reputation System; Experiment